The Effect of Delivery Duration and Drug Price on Consumer Satisfaction at Private Pharmaceutical Wholesale Distributor in Tangerang, Banten-Indonesia - Ilham Arief; LM. Zulfahrin UZ; Dwi Muliati (CV. Media Digital Publikasi Indonesia, 2026)
Pharmaceutical wholesale distributors are critical intermediaries in Indonesia's healthcare supply chain. At PT Cipta Viriya Guna, delivery delays beyond the 24-hour service window and price-related complaints contributed to a 4% consumer and revenue decline in peak months of 2024. Despite this operational context, no prior study has simultaneously examined delivery duration and drug price as predictors of consumer satisfaction in a private PBF setting in Indonesia. Objective: To analyze the partial and simultaneous associations of delivery duration and drug price with consumer satisfaction at PT Cipta Viriya Guna, Tangerang, Banten. A quantitative cross-sectional survey was conducted with 193 institutional clients selected via systematic random sampling (April-May 2025). Validated Likert-scale instruments were used (Cronbach's alpha: 0.917, 0.860, 0.910). Multiple linear regression with classical assumption testing was applied. Delivery duration was significantly and negatively associated with consumer satisfaction (beta = -0.389, t = -6.262, p = 0.000); drug price was significantly and positively associated with satisfaction (beta = 0.507, t = 8.166, p = 0.000). Simultaneously, both variables explained 31.2% of satisfaction variance (F = 43.015, p = 0.000; R = 0.558; Adjusted R2 = 0.305). Delivery duration and drug price are significant predictors of consumer satisfaction in pharmaceutical wholesale distribution.